Alternative tools to investigate HBV entry pathway and intra-host evolution - Goddard, Chun (2021)
Hepatitis B virus (HBV) infects liver cells resulting in hepatitis B infection. In approximately 90% of childhood infections and 10% of adult cases the virus establishes a chronic, lifelong infection. In 2015, it was estimated that approximately 3.5% of the global population were living with chronic HBV infection. Long-term complications of chronic HBV infection such as cirrhosis and hepatocellular carcinoma cause a significant disease burden. The World Health Organisation has set a goal to eliminate the infection by 2030. However, current treatment for HBV does not cure the infection, and most people require the treatment for life. Therefore, a better understanding of the virus lifecycle and viral intra-host evolution is crucial in the development of antiviral drugs.